Design, Synthesis, Molecular Docking, and Biological Evaluation of Pyrazole Hybrid Chalcone Conjugates as Potential Anticancer Agents and Tubulin Polymerization Inhibitors - Md. Jahangir Alam; Ozair Alam; Ahmad Perwez; Moshahid Alam Rizvi; Mohd Javed Naim; Vegi G. M. Naidu; Mohd Imran; Mohammed M. Ghoneim; Sultan Alshehri; Faiyaz Shakeel (MDPI AG, 2022)
Some (E)-3-(3-(4-(benzyloxy)phenyl)-1-phenyl-1H-pyrazol-4-yl)-1-phenylprop-2-en-1-one conjugates 5a-r were designed; synthesized; characterized by 1H, 13C NMR, and ESI-MS; and evaluated for tubulin polymerization inhibitory activity and in vitro cytotoxicity against breast (MCF-7), cervical (SiHa), and prostate (PC-3) cancer cell lines, as well as a normal cell line (HEK-293T). The compounds were also tested to determine their binding modes at the colchicine-binding site of tubulin protein (PDB ID-3E22), for in silico ADME prediction, for bioactivity study, and for PASS prediction studies. Among all the synthesized conjugates, compound 5o exhibited excellent cytotoxicity with an IC50 value of 2.13 ± 0.80 µM (MCF-7), 4.34 ± 0.98 µM (SiHa), and 4.46 ± 0.53 µM (PC-3) against cancer cell lines. The compound did not exhibit significant toxicity to the HEK cells. Results of the in silico prediction revealed that the majority of the conjugates possessed drug-like properties.